Development of an Inertial Measurement Unit based Finger Flexion Measurement System for Functional Electrical Stimulation based Finger Assistive System - Condor, Clyde Matthew Y.; Cañete Jr., Luis Gerardo S. (International Journal of Computing Sciences Research, 2023)
Purpose – This research study examines the use of Inertial Measurement Unit (IMU) sensors for measuring finger range of motion (ROM) as an initial phase towards the creation of an effective feedback system for FES applications. Method – In this paper, a mounting system for IMU sensors designed for stroke patients has been developed. A calibration technique and an orientation estimation algorithm for IMU sensors was developed and validated using Single IMU data validation. Finally, a joint angle measurement system is developed and validated using motion capture analysis. Results – For the Single IMU data validation, the resulting RMSE of the Euler angles pitch, roll, and yaw are 0.96°, 0.76°, and 2°, respectively. The RMSE of the developed IMU-based joint angle measurement system is at 5.3° with a Pearson Correlation Coefficient of 0.9979. Conclusion – The developed calibration procedure and orientation estimation algorithm for the IMU sensors have great performance, as indicated by the single IMU data validation results, while the Joint Angle Measurement Validation results shows that the method is already sufficient for FES applications. The proposed measurement system has the potential for effectively monitoring finger rehabilitation progress for FES applications. Recommendations – There are systematic offsets observed in the validation data results, this can be caused by the imperfect attachment of the markers and can be fixed by improving the motion capture analysis calibration.